Época de supressão da irrigação e manejo pós-colheita: efeitos na produtividade do arroz na qualidade da água, de grãos e sementes - Soares, Camille Flores (2020)
Proper management of irrigation in flooded rice contributes to high levels of grain quality and yield. However, the flood irrigation system, which is predominant in Rio Grande do Sul, by the volume of water used, provides low water use efficiency and due to the long period of flooding causes a great methane emission. In this context, an early irrigation withholding can be an alternative for saving water in the crop season and reduce greenhouse gas emissions. Likewise, post-harvest management of the area affects environmental impact, such as greenhouse gas emissions as well as contamination of water sources. Thus, the present study aims to evaluate the physical and physiological quality of seeds and grains, as well as the physicochemical properties of water (Article I), besides to evaluate greenhouse gas emissions and water quality in function of drainage periods after post-harvest management (Article II). The experiment I was conducted in a field in two municipalities of Rio Grande do Sul. In Cachoeira do Sul at the Estação de Pesquisa do Instituto Riograndense do Arroz (2017/18 and 2018/19 crop season), and in Santa Maria (2018/19 crop season) in the lowland experimental area of the Federal University of Santa Maria (UFSM). The treatments were composed by irrigation withholding moments (R4, 7, 14, 21, 28 and 35 days after R4), in an experimental randomized complete block design with four replications. Experiment II was conducted in Santa Maria after rice harvest, with an experimental randomized complete block design and with different water drainage moments after the knife roller (0, 3, 6, 9 and 12 days) and a treatment with harvest in dry land. Based on the main results achieved, we can observe that irrigation withholding at 14 days after flowering does not affect the physiological quality of seeds, as well as the physical quality and grain yield, and in the case of drainage, it reduces nutrient loss and total solids. During off-season, drainage performed for three days after the use of the knife roller reduces potassium loss and soil particle through drainage water, the shorter period of flooding reduces CH4 emission as well the global warming potential. The rate of decomposition of plant residues is accelerated by the incorporation of straw into the soil, but it is harmed by high rainfall volumes.